Proteolytic activity and cooperative hemolytic effect of dermatophytes with different species of bacteria - Keyvan Pakshir; Tooba Mohammadi; Hossein khodadadi; Mohammad Motamedifar; kamiar Zomorodian; Saeideh Alipour; Marjan Motamedi (Mazandaran University of Medical Sciences, 2016)
Background and Purpose: Globally, dermatophytes are the most common filamentous group of fungi causing cutaneous mycoses. Dermatophytes were shown to secrete a multitude of enzymes that play a role in their pathogenesis. There is limited data on co-hemolytic (CAMP-like) effect of different bacterial species on dermatophyte species. In this study, we sought to the evaluate exoenzyme activity and co-hemolytic effect of four bacteria on clinical dermatophytes isolated from patients in Shiraz, Iran. Materials and Methods: A total of 84 clinical dermatophyte species were isolated from patients suffering dermatophytosis and identified by conventional methods. Hemolytic activity was evaluated with Columbia 5% sheep blood agar. Proteolytic activity was determined by plate clearance assay method, using gelatin 8% agar. CAMP-like factor was evaluated with four bacteria, namely, S. areus, S. saprophyticus, S. pyogenes, and S. agalactiae. Fisher's exact test was run for statistical analysis. Results: T. mentagrophytes was the most predominant agent (27 [32.1%]) followed by T. verrucosum (20 [23.8%]), T. tonsurans (10 [11.9%]), Microsporum canis (7 [8.3%]), T. rubrum (6 [7.1%]), E. floccosum (6 [7.1%]), M. gypseum (5 [6%]), and T. violaceum (3[3.6%]). The most common clinical area of dermatophytosis was the skin. All the isolates expressed the zone of incomplete alpha hemolysis. All the isolates had CAMP - positive reaction with S. aureus and the other bacteria were CAMP-negative. All the isolates expressed proteolytic activity and no significant differences were noted among diverse genera of dermatophytes and severities of proteolytic activity. Conclusion: This study indicated that hemolysin and proteolytic enzymes potentially play a role in dermatophyte pathogenesis and S. aureus could be considered as a main bacterium for creation of co-hemolytic effect in association with dermatophyte species.